The Composition and Structure at Wan Abdul Rachman Park Conservation Area, Lampung - Istomo, Istomo; Ferliana, Erika (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2024)
According to Law No. 5 of 1990 Grand Forest parks are conservation forests that function as nature conservation areas for the purpose of collecting natural and non-natural plants and animals, which are used for research, science, education that support cultivation, culture, tourism and recreation. The purpose of this study was to analyze the composition and structure of the stands in TAHURA Wan Abdul Rachman, Lampung in protection blocks, utilization blocks and collection blocks. The results of this study indicate that the number of species in the collection block is higher than the utilization and protection block. The species that dominated the three research blocks were Dalbergia latifolia, Durio zibethinus, and Tristaniopsis merguensis. The index value of species diversity (H') in the three blocks at the level of seedlings, saplings, poles and trees is in the medium criteria with a value of H'> 2, while the richness index is in the low category. Stratification of Tahura Wan Abdul Rachman's crown is in stratum B and C. Keywords: composition, dominant index, dominant species, vegetation structure, weath index